Analisis Sosial Ekonomi dan Pendapatan Usahatani Buncis Blue Lake di Kecamatan Ngablak Kabupaten Magelang - Ahmad Abidin Ali; Shofia Nur Awami; Indah Arum Ganestyani; Lutfi Aris Sasongko (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Ngablak District is an agropolitan area located on the slopes of Mount Merbabu, which has abundant natural resource potential, such as vast agricultural land for horticultural crops. Blue lake beans are one of the horticultural crops cultivated in Ngablak District with a partner system of PT. X. This study aims to determine blue lake bean farmers' socio-economic characteristics, bean cultivation, and income levels. The number of farmers involved was 44 farmers. The analysis method in this study was a descriptive quantitative analysis method. The results showed that the socio-economic characteristics of farmers were the average age of 42 years, the level of education of farmers was high school or equivalent, the number of family members of farmers was two people, and some farmers also had other jobs besides farming beans. Blue Lake bean cultivation activities include land preparation, planting, weeding, harvesting, and post-harvest. The bean cultivation system used by farmers used monoculture and multiculture cultivation. The average production cost incurred by farmers for bean farming is IDR1,259,071/planting season, with IDR2,364,432/planting season revenue. The average income of farmers is IDR1,287,753/planting season.